Aphonia after shoulder surgery: case report - Moreno,Carlos Alberto da Silva Soares (2016)
ABSTRACT In this case report we highlight the uniqueness of aphonia as, to the best of our knowledge, cases of aphonia related to interscalene brachial plexus block (IBPB) are not described in the literature. Although hoarseness is a common complication of IBPB, aphonia is not. Therefore, we think it is important to publicize the first case of aphonia after IBPB, which may have arisen only because of a recurrent laryngeal nerve chronic injury contralateral to the IBPB site.